Assessing The Effects of Structure and Conduct on The Performance of Fried Onion SMEs - Aina Suciati; Irma Suryahani; Suharno Suharno (Jurnal Ekonomi Pembangunan, 2022)
This study aims to analyze the form of market structure in the Fried Onion Industry in Kuningan Regency and to analyze the effect of capital intensity as an indicator of market structure, the effect of Capital Labor Ratio (CLR), and advertising intensity as an indicator of industrial behavior, and the effect of internal efficiency (Xeff) on Price Cost Margin (PCM) as an indicator of industrial performance in the Fried Onion Industry in Kuningan Regency. This study uses multiple linear regression as quantitative analysis. Based on the research and data analysis results, the market structure formed in the Fried Onion Industry in Kuningan Regency is monopolistic competition, with the concentration ratio of the four largest companies (CR4) at 28.76 percent. Based on the results of regression analysis: it shows that capital intensity has no positive and significant effect on price-cost margin (PCM), capital-labor ratio (CLR) has a positive and significant impact on price-cost margin (PCM), advertising intensity has no positive and significant effect on price-cost margin (PCM), and internal efficiency (Xeff) have a positive and significant impact on the price-cost margin (PCM) in the Fried Onion Industry in Kuningan Regency. To increase the Price Cost Margin (PCM), the Fried Onion Industry in Kuningan Regency must continue to improve its internal efficiency. It is necessary to increase the use of production machines.